Efficient three dimensional modelling of additive manufactured textiles - Guy Bingham; Richard J.M. Hague (2013)
Purpose – To investigate, develop and validate a three dimensional modelling strategy for the efficient generation of conformal textile data suitable for Additive Manufacture. Design/methodology/approach – A series of Additive Manufactured textiles samples were modelled using currently available Computer Aided Design software to understand the limitations associated with the generation of conformal data. Results of the initial three dimensional modelling processes informed the exploration and development of a new dedicated efficient modelling strategy that was tested to understand its capabilities. Findings – The research demonstrates the dramatically improved capabilities of the developed three dimensional modelling strategy, over existing approaches by accurately mapping complex geometries described as STL data to a mapping mesh without distortion and correctly matching the orientation and surface normal. Originality/value – To date the generation of data for AM textiles has been seen as a manual and time-consuming process. The research presents a new dedicated methodology for the efficient generation of complex and conformal Additive Manufactured textile data that will underpin further research in this area.